Epidemiological findings and risk factors for endometrial cancer patients - Anahita Hamidi Layen; Zohreh Yousefi; Behrouz Davachi; Amir Hosein Jafarian; Negar Morovatdar; Helena Azimi; Farnaz Hadavi; Yasaman Nikooiyan; Tahereh Zavvari (Mashhad University of Medical Sciences, 2019)
Introduction: Endometrial cancer is the most common gynecologic malignancy in the world. The most important factor in managing of this malignancy is early detection of the disease and the proper management either by surgery or radiation therapy. This study was performed with aim to evaluate the epidemiology and risk factors of patients with endometrial cancer. Methods: In this cross-sectional study, 53 endometrial cancer patients (endometrioed typing) referred to the gynecology oncology clinic of an academic hospital in Mashhad University of Medical Sciences within 18 months from 2017-2018 were assessed. The standard questionnaire of risk factors for endometrial cancer was completed for all the patients. Data were analyzed by SPSS software (version 25) and kapa test. PResults: In family history of most patients (92.45%), there were no endometrial-related cancers. Blood pressure was the most commonly associated illness in this study. There was no significant difference between mean endometrial thickness in postmenopausal and non-menopausal women (p= 0.134). In terms of risk factors, menopause, weight gain and increased number of pregnancies, there was more increase in these patients. Conclusion: Emphasizing on preventive measures which are available for endometrial cancer and minimizing the risk factors associated with this malignancy are effective in reducing the mortality resulting from this cancer.